Movements of Community-led Initiatives for Regenerative (Post-)Development: Towards a Political Economy of Framing and Resource Mobilization - Esteves, A. (Seminaire CriDIS et CIRTES, 2021)
Regenerative development as an institutional field How CLIs networks construct themselves as political actors : § Co-construction of the field embedded in a relationship of reciprocal influence between public institutions and the economy, whose terms are contested by CLI networks (Lemaître 2009): § Inclusion in the public debate on the sustainability of ecosystems and human settlements § Institutional recognition of CLIs and their networks as organizations and political actors § Inclusion in relevant public policies § “Horizontal understanding of power. How actors engage with resources, structures and systems in different ways.” (Avelino 2017: 506). § Structures of governance § Aggregation and framing of member’s claims § Resource mobilization § Strategic linkages